Green Data Center Design of Udayana University - Rusdiana, Komang Ery; linawati, linawati; Widyantara, I Made Oka (Jurnal Teknologi Elektro, 2016)
Data center of Udayana University is not integrated who caused excessive power usage. The green data center system needs to be applied to the data center of Udayana University, where the use of power can be more efficient and environmentally friendly. The purpose of this study is to determine the energy consumption in the data center of Udayana University and to design a data center in accordance with the criteria and standards for green data center. Collecting data in this study using the survey directly into the data center, interviews with IT staff and analyze the data center. Then, will be calculated green metrics i.e. Power Usage Effectiveness (PUE) and Data Center Infrastructure Efficiency (DCIE) and designing a green data center. Based on the research, the result of data center power consumption is 104.231 w. where the results of the calculation of PUE is 2.51 which is inefficient and DCIE calculation is 39%, which means that the efficiency of power usage reaches 39%. From the results obtained, will be redesign the servers clustering to minimize the use of cables and easier for checking, using a raised floor according to the cooling system was designed, using a system of electric 3 phase for load balanced, redesign the cooling system using a row-oriented cooling system and redesign cabling in the data center. By doing the design of green data center at the University of Udayana, data center power consumption will be down significantly and efficiency will be increased.
Keywords: green data center, green metrics, Power Usage Effectiveness, Data Center Infrastructure Efficiency, row oriented cooling system